Women's Rights in Rejecting Polygamy: Islamic Law Perspective and Compilation of Islamic Law in Indonesia - Ledianto, Fajar; Khalilullah; Muis, Muhsin (Jurusan Hukum Acara Peradilan dan Kekeluargaan, 2024)
Abstract Polygamy is an inevitability that must be accepted by every individual who holds firmly to the tenets of Allah's religion, Islam. Islam regulates the issue of polygamy in great detail to maintain balance, justice, order, and to avoid tyranny. The Sharia on polygamy came down with the spirit of reducing quantity, not the opposite, through a very strict mechanism of justice. Unlike the pre-Islamic culture that legalized men to marry an unlimited number of wives, Islam limits a man to marry only up to four women. Additionally, Islam also grants women or their guardians the right to accept or reject polygamy. For instance, the Prophet Muhammad (peace be upon him) prohibited Ali ibn Abi Talib from marrying another woman while still married to his beloved daughter Fatimah. This research methodology uses a qualitative approach with an exploratory type. This study will examine two things: first, the analysis of the limits of polygamy from the perspective of fiqh law and the Compilation of Islamic Law (KHI). Second, women's right to refuse polygamy. The results of this study are, firstly, that polygamy is prescribed based on the principle of maslahat (benefit), hence religion grants wives the right to accept or refuse polygamy.